Use of benzylglycinamide by a HIV-seropositive polysubstance user: The changing pattern of novel psychoactive substance use among youths. (September 2016) - Caloro, Matteo; Calabrò, Giuseppa; Kotzalidis, Georgios D.; Cuomo, Ilaria; Corkery, John M.; Vento, Alessandro Emiliano; Lionetto, Luana; De Filippis, Sergio; Ranieri, Valentina; Lonati, Davide; Locatelli, Carlo Alessandro; de Pisa, Eleonora; et al.
Abstract: A 24-year old woman with multisubstance use since the age of 13, including opioids and cocaine, and long-standing HIV/HCV seropositivity status, presented with psychosis, agitation, and insomnia at the emergency department of a university hospital. She had been abusive and physically aggressive frequently without specific reasons and was involved in criminal legal cases. She was hospitalized twice. During her first hospital stay she experienced a brief episode of detachment from her environment, similar to episodes reportedly suffered at home. Psychosis had developed following heavy polysubstance abuse. Her mother provided sachets containing benzylglycinamide, a substance with no known psychotropic effects, which were also present in the patient's urine. She was occasionally positive for cannabinoids. She used to buy various novel psychoactive substances (NPSs) from the internet and used experimentally various substances freely made available to her by drug suppliers/dealers. She was unable to explain clearly why she was taking any of the identified NPS. She stated she was taking benzylglycinamide to calm her when smoking synthetic cannabinoids. While it appears that benzylglycinamide is not likely to constitute a novel drug of abuse, her polysubstance use exemplifies trends in NPS use patterns among the youths in the Western world and should alert mental health workers as to the possible dangers of such behavior and its reflection on social behavior and psychopathology. Highlights: Benzylglycinamide (BGA) has never been reported as a drug of abuse. We report on a patient with psychosis with documented BGA abuse. Patient claimed that the addition of BGA to cannabinoids helped her relax.